Efeitos da exposição ao di-(2-etilhexil)-ftalato no processo da amelogênese, utilizando o modelo experimental em roedores - Ribeiro, Alesandra Thainara (2023)
Tooth enamel is a mineralized tissue and, when mature, is characterized by a lack of metabolic activity. This means that any disturbance during its formation can manifest itself as a permanent defect in the erupted tooth. Molar-incisor hypomineralization (MIH) is a multifactorial pathology, in which environmental factors have been identified as important causative agents, with great emphasis on endocrine disruptors, substances that interfere with the body's homeostasis and may interfere with the development of tooth enamel, interfering with the Androgen signaling during amelogenesis. The ill of this study is to evaluate the effects of exposure to di-(2-ethylhexyl)-phthalate (DHEP), during pregnancy and lactation, on the amelogenesis process of male offspring of Wistar rats. For this purpose, 10 pregnant rats were separated into 3 experimental groups (n=10/group) and treated by gavage (from the 8th day of pregnancy until weaning), as follows: Group 1: 10 mg of di- (2-ethylhexyl)-phthalate (DHEP)/kg; Group 2: 30mg of DHEP mg/kg, and Group 3: control, corn oil. After birth, parameters related to physical development milestones of male offspring were evaluated in different experimental groups. At the end of the experimental period, male pups were euthanized at the following ages: 1 day (pre-ameloblast stage), 5 days (secretion stage), and 10 days (maturation stage). The heads were fixed in 4% paraformaldehyde, embedded in paraplast, sectioned at 5µm, stained with hematoxylin/eosin and analyzed for morphometric parameters. Maternal treatment with DEHP did not alter the somatic developmental milestones of the exposed offspring. However, morphometric parameters related to the enamel organ were reduced in the offspring of groups G2 and G3, compared with the offspring of G1. Enamel matrix thickness was similar between groups. It is concluded that exposure to DHEP during pregnancy and lactation may interfere in height of ameloblast during the secretion phase of amelogenisis